Percutaneous Atrial Septal Defect Closure Using the Occlutech Figulla Device in Adults: More than 800 Patient-Years of Follow-Up - R. J. R. Snijder; L. E. Renes; D. Bosshardt; M. J. Suttorp; J. M. ten Berg; M. C. Post (Journal of Interventional Cardiology)
Purpose. The Occlutech Figulla occluder has been proven safe and effective at midterm follow-up after percutaneous atrial septal defect (ASD) closure. We describe the safety and efficacy at long-term follow-up in adults. Methods. All consecutive adult patients that underwent ASD closure between 2008 and 2015 were included. All complications were registered. Residual left-to-right shunt (LRS) was diagnosed using color-Doppler transthoracic echocardiography (TTE). Right-to-left shunting was diagnosed using contrast TTE. Successful closure was defined as no LRS at follow-up. Results. In total, 166 patients (mean age 56.7 ± 16.1 years; 62% female) underwent percutaneous ASD closure using the Occlutech Flex I (70%) or Flex II (30%) device (diameter 24 mm; range 10–40 mm) under general anaesthesia and transoesophageal echocardiographic guidance. Long-term follow-up data were available for 144 patients (87%) with a mean follow-up of 5.9 ± 2.6 years, a total of 814 patient-years. During hospitalization, device embolization occurred in three patients (1.8%) with successful extraction in all. During the long-term follow-up, 15 patients (9.8%) suffered new-onset atrial fibrillation and stroke occurred in 2.1%. There was no residual LRS at 12-month follow-up. No device embolization occurred during the long-term follow-up. Conclusion. Percutaneous ASD closure using the Occlutech device appears to be safe at long-term follow-up with a high successful closure rate at one year.